2018
DOI: 10.1093/ofid/ofy042
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Reported Penicillin Allergy on Mortality in MSSA Bacteremia

Abstract: BackgroundPenicillin allergy frequently impacts antibiotic choice. As beta-lactams are superior to vancomycin in treating methicillin-susceptible Staphylococcus aureus (MSSA) bacteremia, we examined the effect of reported penicillin allergy on clinical outcomes in patients with MSSA bacteremia.MethodsIn this retrospective cohort study of adults with MSSA bacteremia admitted to a large tertiary care hospital, outcomes were examined according to reported penicillin allergy. Primary outcomes included 30-day and 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…Of the 20 studies examining LOS, 11 (55%) found that allergy-labeled patients had significantly longer LOS. 2,19,20,25,29,30,[36][37][38][39][40] Also, 8 studies found equivocal results and 1 found that allergy-labeled patients were hospitalized for shorter duration. 17,21,23,24,[31][32][33]41,42 Of 6 studies, 1 (17%) found that allergylabeled patients were more likely to be admitted to the ICU, but all other studies reported no difference (Table 3).…”
Section: Antibiotic Allergy Labels and Clinical Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 20 studies examining LOS, 11 (55%) found that allergy-labeled patients had significantly longer LOS. 2,19,20,25,29,30,[36][37][38][39][40] Also, 8 studies found equivocal results and 1 found that allergy-labeled patients were hospitalized for shorter duration. 17,21,23,24,[31][32][33]41,42 Of 6 studies, 1 (17%) found that allergylabeled patients were more likely to be admitted to the ICU, but all other studies reported no difference (Table 3).…”
Section: Antibiotic Allergy Labels and Clinical Outcomesmentioning
confidence: 99%
“…Turner et al, 2018 40 Patients with a penicillin allergy label were more likely to receive vancomycin (38% vs 11%; P < .01) and were less likely to receive nafcillin (5% vs 45%; P < .01). Allergy-labeled patients were more likely to have an infectious disease consult (74% vs 58%; P = .02).…”
Section: Not Assessedmentioning
confidence: 99%
“…5,6 Although most reactions following use of penicillin and related antibiotics are not true drug allergies, medical practitioners often prescribe less effective or more expensive alternatives. [7][8][9] This leads to an increased risk of adverse events, more drug-resistant organisms and more Clostridium difficile infections. 10,11 Presently, primary care providers struggle to rule out penicillin drug allergies.…”
mentioning
confidence: 99%
“…Turner et al performed a retrospective cohort assessing the outcomes in patients with and without β-lactam allergies and MSSA BSI and found patients with β-lactam allergies were more likely to receive definitive therapy with vancomycin ( P < .01). 10 The authors also found no difference in 30-day ( P = .99) or 90-day ( P = .47) all-cause mortality between groups, but receipt of a β-lactam was protective toward 30-day (adjOR, 0.26; 95% CI, 0.12-0.54) and 90-day (adjOR, 0.41; 95%CI, 0.21-0.81) mortality, which is similar to the current study. While 44% of β-lactam allergic patients still received a β-lactam, the authors concluded that a reported penicillin allergy only matters if it prevents a patient from receiving a β-lactam.…”
Section: Discussionmentioning
confidence: 99%
“…6 -8 Nonsevere or falsely reported β-lactam allergies represent an important barrier to receiving optimal therapy for MSSA BSI, but data surrounding this influence on patient outcomes are limited. 8 -10…”
Section: Introductionmentioning
confidence: 99%